Analysis of the impact of COVID-19 pandemic on women´s care in an abortion situation in Latin America and the Caribbean - Rodolfo Gomez Ponce de Leon; Luiz Francisco Baccaro; Gonzalo Rubio Schweizer; Suzanne Jacob Serruya (Oswaldo Cruz Foundation, Health Law Program, 2023)
Objective: to understand the influence of the COVID-19 pandemic on aspects of quality of care provided to women in abortion situations in sentinel centers of the CLAP MUSA-Network (a multicenter network with international cooperation with the aim of encouraging good practices in Latin America and the Caribbean). Methods: cross-sectional study between January/2017 and December/2021 with women of any age admitted for abortion or miscarriage. We analyzed the total number of cases and the proportion of legal abortions. The dependent variables were complications and use of contraceptives after abortion. The independent variables were COVID-19 pandemic, clinical and sociodemographic data. Statistical analysis was carried out using linear regression, multiple Poisson regression, Cochran-Armitage, chi-square, Mann-Whitney and Cohen tests. Results: we analyzed data from 93689 women assisted in 12 sentinel centers of the CLAP MUSA-Network, 64.55% in the pre-pandemic period (NP) and 35.45% in the pandemic period (PP) (22.73% received post-abortion care and 77.27% legal abortion). We found no differences in the number of cases over the period, regardless of the legal context. We observed a significant increase in the proportion of legal abortions in liberal and moderate contexts. In NP, 46.46% of women underwent medical abortion, while 62.18% of women underwent medical abortion in PP (h-Cohen 0.32). We found no increase in the number of complications during PP. In NP, 79.12% started contraceptives after abortion, while in PP, 70.39% started contraceptives after abortion (h-Cohen 0.20). Conclusion: the COVID-19 pandemic was not associated with a decrease in the number of cases, a decrease in the proportion of legal interruptions, or an increase in complications in sentinel centers of the CLAP MUSA-Network. Submission: 30/04/23|Review: 08/11/23|Approval: 09/11/23